Differential mRNA transcription during salinity stress in barley - Ramagopal, Subbanaidu (1987)
The molecular and genetic bases of salinity tolerance in plants are not understood. Gene expression at the mRNA level was investigated in a salt-tolerant and a salt-sensitive genotype of barley. Seedlings were exposed to NaCl stress and translatable mRNAs were isolated from root and shoot tissues. A reticulocyte cell-free system was programed with barley mRNAs and the in vitro products were resolved on two-dimensional polyacrylamide gels following isoelectric focusing or nonequilibrium pH gradient gel electrophoresis in the first dimension. The functional mRNAs in unstressed seedlings were qualitatively almost indistinguishable in the two genotypes. However, salinity stress triggered differential transcription of specific mRNAs depending upon genotype and tissue. In roots, 12 new mRNAs were induced that encoded proteins of 21-34 kDa, with a pI range of 6.1-7.7. In shoots, the 9 new mRNAs coded for proteins of 18-50.5 kDa, with a pI range of 5.4-7.8. These new stress mRNAs represented one of two main classes. Class I consisted of mRNAs shared by both genotypes. Class II represented mRNAs specific to each genotype; unique mRNAs of roots accumulated preferentially in the salt-tolerant genotype, whereas those of shoots accumulated in the salt-sensitive genotype. The findings suggest that transcriptional as well as posttranscriptional mechanisms regulate gene expression in barley during salinity stress.